2006
DOI: 10.5188/ijsmer.14.7
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Developing High Performance Al-Li Alloys

Abstract: The goal of replacing 'conventional' Al alloys with Al-Li alloys to reduce weight of aerospace structures has had only limited success to date, despite one of the largest alloy-development programs ever undertaken. One of the reasons being, for some product forms and crack-plane orientations, fracture toughness is lower compared with conventional Al alloys due to a greater propensity for low-energy intergranular fracture. Proposed explanations for brittle intergranular fracture include: (i) planar slip resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…11 e. This means that AA8090 displayed anisotropy in its tensile properties. Moreover, the degree of anisotropy in the tensile properties of AA8090 was higher than that in AA1420, the finding which is in line with those reported in previous investigations [97] , [98] , [99] . Anisotropic tensile properties (through-thickness anisotropy and in-plane anisotropy) are a pivotal issue that has received much attention in 2 nd generation Al-Li alloys, particularly anisotropy in the ductility, yield, ultimate strength and fracture toughness as depicted in previous figures.…”
Section: Anisotropic Behavior Of the Al-li Alloyssupporting
confidence: 92%
“…11 e. This means that AA8090 displayed anisotropy in its tensile properties. Moreover, the degree of anisotropy in the tensile properties of AA8090 was higher than that in AA1420, the finding which is in line with those reported in previous investigations [97] , [98] , [99] . Anisotropic tensile properties (through-thickness anisotropy and in-plane anisotropy) are a pivotal issue that has received much attention in 2 nd generation Al-Li alloys, particularly anisotropy in the ductility, yield, ultimate strength and fracture toughness as depicted in previous figures.…”
Section: Anisotropic Behavior Of the Al-li Alloyssupporting
confidence: 92%
“…The 2nd generation alloy's tensile properties depend upon the loading directions, where the Fs and UTS values are higher than for those 90°and 45°directions, which can be observed from figures 4(a) and (b). Which is conclude that anisotropy was higher in the 2nd generation than the 1st generation in tensile properties by different investigations [68][69][70]. These anisotropy properties were reported and highlighted more in the 2nd generation as they received particular attention, which dominates some of the properties like ductility, yield, ultimate, and fracture toughness [71][72][73].…”
Section: Tensile Properties Of 2nd Generation Alloysmentioning
confidence: 82%
“…High‐entropy alloys made by this method are significantly more robust and ductile than other casting methods, and the rupture strength can reach 1400 MPa, which is six times the strength of 304 stainless steel used in traditional engines. In 2021, Pasang et al [ 98 ] investigated the mechanical characteristics of Ti–6Al–4 V prepared by AM technologies and found that EBM samples have higher surface roughness than SLM samples. The development of new materials for EBM has also progressed.…”
Section: Powder‐based Methodsmentioning
confidence: 99%
“…However, due to the equipment's poor production speed, the shortcomings of powder performance, and the inefficient manufacturing industry chain, SLM still has the space for the following developments. [98,99] 1) Developing purer and more refined powders, optimizing their overall qualities such as particle size, thermophysical properties, and developing a suitable manufacturing method to eliminate spheroidization, warpage deformation, and fractures in treated components. [83] 2) Accelerating research on large-part SLM moulding.…”
Section: Research Focus and Prospects Of Slmmentioning
confidence: 99%